Immune-checkpoint inhibitors in brain metastases from renal cell carcinoma: a battle was lost but not the war - Lombardi, Giuseppe; Maruzzo, Marco; Minniti, Giuseppe; Padovan, Marta; Caccese, Mario; Zagonel, Vittorina (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Immune-checkpoint inhibitors have recently changed the landscape treatment for metastatic clear cell renal-cell carcinoma (ccRCC) since they showed to be effective in disease control and survival improving. In particular, the programmed death 1 (PD-1) checkpoint inhibitor nivolumab demonstrated efficacy in two phase 3 studies analyzing patients with both alone and in association with ipilimumab (1,2). However, patients with brain involvement were not enrolled and this clinical setting represents a treatment challenge for physicians.